AMPK activation induced by promethazine increases NOXA expression and Beclin-1 phosphorylation and drives autophagy-associated apoptosis in chronic myeloid leukemia. (5th January 2020) - Medeiros, Hyllana C.D.; Colturato-Kido, Carina; Ferraz, Letícia S.; Costa, Claudia A.; Moraes, Vivian W.R.; Paredes-Gamero, Edgar Julian; Tersariol, Ivarne L.S.; Rodrigues, Tiago
Abstract: Relapse and drug resistance is still major challenges in the treatment of leukemia. Promethazine, an antihistaminic phenothiazine derivative, has been used to prevent chemotherapy-induced emesis, although there is no report about its antitumor potential. Thus, we evaluated the promethazine cytotoxicity against several leukemia cells and the underlying mechanisms were investigated. Promethazine exhibited potent and selective cytotoxicity against all leukemia cell types in vitro at clinically relevant concentrations. Philadelphia positive chronic myeloid leukemia (CML) K562 cells were the most sensitive cell line. The cytotoxicity of promethazine in these cells was triggered by the activation of AMPK and inhibition of PI3K/AKT/mTOR pathway. The subsequent downstream effects were NOXA increase, MCL-1 decrease, and Beclin-1 activation, resulting in autophagy-associated apoptosis. These data highlight targeting autophagy may represent an interesting strategy in CML therapy, and also the antitumor potential of promethazine by acting in AMPK and PI3K/AKT/mTOR signaling pathways. Since this drug is currently used with relative low side effects, its repurposing may represent a new therapeutic opportunity for leukemia treatment. Graphical abstract: Image 1 Highlights: Resistance to chemotherapy is a clinical challenge in leukemia therapy. Antiallergic small molecule promethazine is used as antiemetic in cancer patients. Promethazine induced a selective leukemia cell death through autophagy-apoptosis. For the first time, the antitumor effects of promethazine were described.